DEVELOPMENT OF TABULAR METHOD FOR CALCULATION OF PRIMITIVE FUNCTION IN MODULAR CODE - Vitaly V. Grankin (Вестник Северо-Кавказского федерального университета, 2022)
The item dwells on the solution for tabular calculation of primitive function in modular code, both in view of hardware costs and in view of the processing speed.